Fenomena Iklan Judi Online Pada Platform Digital Generasi Z Di Indonesia - Khresna Adityo Fathor; Fauzan Putra Gani; Mohamad Zein Saleh (Pusat Riset dan Inovasi Nasional, 2024)
Advertising is a communication tool intended to promote goods and services. Advertising through digital platforms such as social media and internet users who are often called influencers is a new mechanism for marketing products and services. This new mechanism creates convenience in advertising, including illegal advertising such as online gambling advertisements. The research was conducted based on the increasing phenomenon of online gambling advertising on digital platforms which are often used by generation Z. The method used in this research was literature study and literature review. It is hoped that this research can explain in detail the phenomenon of online gambling advertising on generation Z digital platforms in Indonesia.